Exploring the concept of pedagogical resilience during the COVID-19 pandemic: Teachers’ perspectives from Thailand and the Philippines - Zara, Celso G.; Balazon, Francis; Wangdi, Thinley; Perales, William Franco; Praditson, Pavirasa; Ulla, Mark Bedoya (Frontiers in Education, 2022)
This brief research report aimed to explore the concept of pedagogical resilience and how teachers in Thailand and the Philippines build resilience in pedagogy during the COVID19 pandemic. Employing the qualitative research design, the data were obtained from the focus group discussion (FGD) and semi-structured interviews with twelve (12) teachers, eight of whom were from one of the universities in the Philippines and another four teachers from a university in Thailand. The thematic analysis revealed that pedagogical resilience is influenced by teachers’ personal, professional, and social attitudes toward teaching and learning during the COVID19 pandemic. Although teachers acknowledged that they had no experience in remote and online teaching, they demonstrated resiliency by being flexible and adaptive to the situation. Such an attitude allowed them to build a relationship with their colleagues and design teaching and learning pedagogy that addresses the issues in their online and remote teaching. The findings provide a clear understanding of the conceptualization of pedagogical resilience from the perspectives of teachers in the Philippines and Thailand.